Enhancing the well-being of children and families through effective interventions : international evidence for practice - McAuley, Colette; Pecora, Peter J.; Rose, Wendy, 1944- (Jessica Kingsley, 2006)
Current government policy is explicitly aimed at increasing opportunities for all children and improving the outcomes for our most vulnerable children.€A fundamental question asked by politicians, policy makers and professionals alike is what do we know about makes a difference? Which services help and in what circumstances? Which are valued by families? Are services effective for children with additional needs because of disability or ethnicity or other factors in their lives?€Answers to these questions are crucial to direct resources where they can bring about tangible improvements.